Analysis of Overcoming Writing Difficulties of Students in Elementary Schools - Febryanda, Dini; Fitriyeni, Fitriyeni (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
There are still some students who attend SDIP YLPI who are under six years old, so teachers must also instill in these students the desire to write independently. As a result, there is a lack of student interest in writing at school. This research wants to explain the writing difficulties faced by students and the role of teachers in overcoming the writing difficulties of class IID students at SDIP YLPI Pekanbaru. This research is a qualitative descriptive research. In this study, data was obtained from 1 IID homeroom teacher and 6 IID class students. Data collection methods used include interviews, observation and documentation. Data processing uses data reduction steps, data presentation, and conclusions in data analysis. Research data shows that the majority of class IID students at SDIP YLPI Pekanbaru have difficulty writing. Some of the problems encountered include unreadable writing, delays in writing, missing or inverted letters, and errors in holding a pencil. Teachers can help students overcome writing difficulties by identifying the problems students face and using interesting and effective learning media, increasing students' self-confidence, providing motivation, and avoiding blaming them for problems that hinder them. Teachers may also offer special remedial writing programs for their students